Exclusion from hexagonal mesophase surfactant domains drives end-to-end enchainment of rod-like particles - Sharma, Kamendra P.; Ganai, Anal Kumar; Sen, Debasis; Bhagavatula L. V. Prasad; Kumaraswamy, Guruswamy (Journal of Physical Chemistry B, 2013)
Anisotropic rod-like particles assemble end-to-end when the surfactant/water matrix in which they are dispersed is cooled from the isotropic to the lyotropic hexagonal phase. We demonstrate the formation of such end-to-end assemblies for gold nanorods, which are tens of nanometers in size, as well as for micrometer-sized ellipsoidal polystyrene particles. In both cases, the particles are well-dispersed in the low-viscosity surfactant/water phase above the isotropic-H-1 transition temperature. On cooling into the H-1 phase, mesophase domains form and the particles are expelled to the isotropic phase. As the H-1 domains grow and finally impinge, the particles are localized at the domain boundaries where they reorient and assemble end-to-end. Remarkably, we observe the formation of end-to-end assemblies of gold nanorods even for volume fractions as low as 2 x 10(-6) in the initially dispersed state. The extent of particle ``enchainment'' increases with the particle concentration and with the aspect ratio of the particles.